Arylsulfatase Activity in the Gut Microflora of Fish and Shellfish of Veli Lake, Kerala - K., Dhevendaran; K., Maya (Fishery Technology, 2025)
Moraxella sp.. Vibrio sp. and Micrococcus sp. were isolated from representative cultures derived from Villorita cyprinoides, Therapon jarbua and Penaeus indicus caught from Veli lake in Kerala (India). pH optimum for Moraxella sp. was at 5.6 whereas it was 7 for Vibrio sp. and Micrococcus sp. Maximum growth of Moraxella sp. and Micrococcus sp. was at pH 5.6 and that of Vibrio sp., at pH 7.0. Optimum temperature for Micrococcus sp. was 29Â°C and for both Vibrio sp. and Moraxella sp., 370C. The elevated arylsulfatase activity in these strains was found to vary with the addition of amino acids, organic and inorganic salts. Of these, phosphate was the key factor determining the type of arylsulfatase and inhibited the enzyme activity at 0.05M concentration in Moraxella sp. and Vibrio sp. and at 0.2M concentration in Micrococcus sp. Optimum buffer molarity was 0.1M when nitrocatechol sulfate was used as the substrate. The growth and enzyme activity of gut microflora were inhibited under growing conditions by the addition of heavy metals. Observations suggest that gut flora decompose esters of sulfuric acid thereby assisting digestion and metabolism of host fish and shellfish.